Estudos populacionais e delimitação específica do complexo de espécies tibouchina pereirae brade & markgraf - Freitas, Juliana Gomes (2017)
A study of morphological and genetic variation within the Tibouchina pereirae species complex, a group of five species endemic to the “campos rupestres” of Chapada Diamantina, is here presented. These species are generally shrubs with leaves grouped at the apex of branches, lilac to purple flowers with dimorphic in size anthers pollinated by large solitary bees, and loculicidal capsules with small seeds dispersed by gravity. These species have different morphotypes with overlapping morphological characters that difficult species delimitation by traditional methodologies. A total of 540 specimens from 27 sampling localities were collected along all the distribution range of the complex. These specimens were analyzed with several methodologies to assess patterns of morphologic and genetic variation in order to infer the evolutionary history of the group, patterns of morphologic and genetic diversity, gene flow, and demographic history. Thus, this is a contribution for the understanding of processes affecting lineage distribution, diversification, evolutionary history, and species delimitation within the species complex. Preliminary results indicated one of those lineages within the complex should be better treated as a different species (Pleroma rubrum) and its formal description is included here. Results from the morphometric analyses showed a relationship between leaf shapes and size among species in the complex. Furthermore, leaf asymmetry analyses revealed patterns not generally included in plant morphologic variation studies. The DNA data indicated high genetic diversity within species and genetic separation between them, despite differences between traditional morphologic delimitation and genetic data for all species. This suggest hybridization and introgression has played and important role in the evolutionary dynamic of the complex. The estimated diversification time of the complex corresponded with the lineage diversification of fire-adapted plants and the expansion of tropical savanna ecosystems dominated by C4 grasses. In addition, results showed that northernmost localities from Chapada Diamantina provably served as refugia for these species during past climatic oscillations